On Approaching the Limit of Molecular Magnetic Anisotropy: A Near‐Perfect Pentagonal Bipyramidal Dysprosium(III) Single‐Molecule Magnet. Issue 52 (22nd November 2016) - Ding, You‐Song; Chilton, Nicholas F.; Winpenny, Richard E. P.; Zheng, Yan‐Zhen
Abstract: We report a monometallic dysprosium complex, [Dy(O t Bu)2 (py)5 ][BPh4 ] (5 ), that shows the largest effective energy barrier to magnetic relaxation of Ueff =1815(1) K. The massive magnetic anisotropy is due to bis‐trans‐disposed tert‐butoxide ligands with weak equatorial pyridine donors, approaching proposed schemes for high‐temperature single‐molecule magnets (SMMs). The blocking temperature, TB  , is 14 K, defined by zero‐field‐cooled magnetization experiments, and is the largest for any monometallic complex and equal with the current record for [Tb2 N2 {N(SiMe3 )2 }4 (THF)2 ]. Abstract : Record‐breaking : A monometallic dysprosium complex, [Dy(O t Bu)2 (py)5 ][BPh4 ], displaying near‐perfect pentagonal bipyramid geometry defined by two strong axial tert ‐butoxide ligands and five weak equatorial pyridine donors is reported. This complex displays massive magnetic anisotropy, approaching the limit of a two‐coordinate complex, with an energy barrier to magnetic relaxation of U eff =1815(1) K and a blocking temperature of T B =14 K.